Impacts of ground slope on main performance figures of solar chimney power plants: a comprehensive CFD research with experimental validation - Cuce, Erdem; Cuce, Pinar Mert; Sen, Harun; Sudhakar, K.; Berardi, Umberto; Serencam, Ugur (Hindawi, 2021)
Geometric parameters in solar chimney power plants are numerically optimised for the purpose of better power output figures. Several parameters have been investigated in the pilot plant such as chimney height and diameter, collector diameter and slope, and slenderness. However, ground slope has not been studied to date despite its perspicuous impact on turbulent flow. In this study, the impacts of the different slope angles of the ground, where the solar radiation is absorbed through the collector, on the main performance parameters of the system are numerically analysed through a reliable CFD software ANSYS FLUENT. By considering the actual geometric figures of the pilot plant, a 3D model is constructed through DO (discrete ordinates) solar ray tracing algorithm and RNG k-ε turbulence model. For the solar intensity of 1000 W/m2, the maximum velocity inside the system is found to be 14.2 m/s, which is in good accordance with the experimental data of 15.0 m/s. Starting from 5 m inside the collector, the chimney inlet heights are reconfigured 0.209, 0.419, 0.625, 0.838, and 1.04 m, respectively, and when the ground slope is 0.1, 0.2, 0.3, 0.4, and 0.5°, the changes in the performance output of the system are investigated. For the reference case which refers to the horizontal ground, the maximum air velocity is determined to be 14.2 m/s and the power output is 54.3 kW. However, when the ground slope is made 0.5°, it is observed that the maximum velocity increases by 37% to 19.51 m/s, and the power output is enhanced to 63.95 kW with a rise of 17.7%. Sloping ground is found a key solution to improve the turbulent effects inside the plant, thus to enhance the electrical power output.